Trends on mexican ethnozoological research, vertebrates case: a systematic review - Gutiérrez-Santillán, Tania Vianney; Albuquerque, Ulysses Paulino; Valenzuela-Galván, David; Reyes-Zepeda, Francisco; Vázquez, Luis-Bernardo; Mora-Olivo, Arturo; Arellano-Méndez, Leonardo Uriel (Ethnobiology and Conservation, 2018)
Systematic reviews and meta-analytical approach are a tool used in different social and biological disciplines, but its application in evaluating ethnobiological information is scarce. Thus, through this analytical approach, we seek to answer if there are any patterns in the mexican ethnozoological scientific production. We searched for studies published between 2005 and 2015 in catalogues, repositories and databases. For evaluating significative differences among seven variable datasets, we first used non parametric Kruskal-Wallis tests and then Tukey multiple comparison tests. We also determined the link between researchers and institutions with a multidimensional non-metric scaling analysis. We found 295 published studies, book chapters were the most representative (27%), diffusion articles (20%), impact factor articles (15%) and indexed articles (14%). There are significant differences in the number of publications among the evaluated years, among thematic areas, study focus (qualitative/quantitative), ethnographic and biological methods. Regarding academic linking, we identified 94 author adscription institutions, however, no research networks were identified. Our results suggest that the amount, diffusion and reach of mexican ethnozoological production show a tendency to non-periodic publishing, predilection for qualitative approach, a low use of statistical and ethnobiological analysis, as well as an inadequate selection of biological methods. We suggest this data analysis approach will allow a better standardization for information taking and processing, aiding the discipline in its growth and consolidation.